(untitled) - The World Bank in VietNam (WB) (Ha Noi, 2004)
The proposed operation would reduce poverty and foster secure and sustainable livelihoods for those living in the country’s poorest and most marginal communes . In particular, it would enhance performance of GoV’s targeted programs with respect to local-level empowerment, transparency and accountability; poverty targeting; and monitoring and evaluation (M&E). Expected key performance indicators would include (to be further specified during preparation): -Empowerment of local communities and ethnic minorities, assessed against their demonstrated capacity in directly managing investments and use of citizen report cards; --Instrumental benefits of empowerment seen in higher quality and cost-effectiveness of basic infrastructure investments in participating, by comparision with those in non-program communes; Poverty targeting as shown by the percentages of poor people included and non-poor excluded, and percentage of program investements that reach or benefit the poorest quintile of the population; Improved process monitoring and impact evaluation mechanisms applied in pratice and used to inform ongoing implementation.
Keywords: Social service, Rural,Guaranteed annual income,Đảm bảo thu nhập hàng năm,Dịch vụ xã hội, Nông thôn; Vietnam,Vietnam,Việt Nam,Việt Nam